Keanekaragaman dan Kelimpahan Serangga di Perkebunan Teh PTPN IV Tobasari Kecamatan Pamatang Sidamanik Kabupaten Simalungun - Angel Tessalonika Napitu; Khairiza Lubis; Lazuardi Lazuardi (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to analyze the diversity and structure of insect communities in tea plants (Camellia sinensis) as the basis for sustainable and environmentally friendly plantation management. The research was conducted at the PTPN IV Tobasari Tea Plantation using an observation method with the installation of yellow sticky traps at five observation points. The results of the study showed that 20 species of insects were found with a total of 402 individuals, with the most species, namely Bactrocera dorsalis. A diversity index value (H') of 2.52 indicates a moderate level of diversity, a dominance index (C) of 0.14 indicates the absence of dominating species, and an evenness index (E) of 0.84 indicates a relatively even distribution of individuals between species. Measured abiotic factors include an average temperature of 29.75°C, light intensity of 3921.17 lux, and wind speed of 6.48 m/s. Ecologically, the combination of H', C, and E values shows that the ecosystem of the Tobasari Tea Plantation is in a fairly stable condition with low to moderate levels of ecological stress, thus supporting the sustainability of the insect community.